Elementary school teachers' attitudes to teamwork - Vasilijević Danijela N.; Stepić Gordana M.; Ilić Marina Ž. (Nastava i Vaspitanje, 2017)
Research to date has shown that teacher teamwork results in higher motivation among students and higher quality knowledge, and also facilitates the sharing of professional experiences and stimulates teachers' creativity and their openness to change. Team forming and development depend on multiple factors, particularly on the individual and group traits of team members. This paper examines teachers' attitudes as an individual factor significant for their inclination for team teaching, and the aim of the study presented in the paper was to study teachers' attitudes to teamwork. The sample consisted of 240 teachers from fifteen elementary schools in Belgrade. Factor analysis has singled out three factors around which teachers' attitudes are grouped: a) teaching; b) team and individual development; and c) professional challenge. The study has shown that overall, teachers have a positive attitude to teamwork because it is conducive to a stimulating environment for work and learning, and also provides an opportunity for teachers' personal and professional development. Significant differences in the perception of teamwork have been noted among lower-grade teachers depending on their years of service and the extent to which they have been engaged in team teaching.